Minerva Alganza Roldán – Álvaro Ibáñez Chacón (eds.), Mythographica Graeca. Transmisión, textos y contextos, Madrid, Dykinson 2023, 292 pp. [ISBN: 9788411707305]. - Lorenzo Maria Ciolfi (Estudios Bizantinos)
Recensione.